2003
DOI: 10.1089/109629603764655236
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis: A New Technique to Monitor Perioperative Human Peritoneal Mediator Production

Abstract: The samples derived from microdialysis were suitable to measure sub-peritoneal mediator profiles during surgery and up to 7 days postoperatively. Microdialysis data should be validated for a potential correlation with the clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Despite the size‐limited passage through the micropores in clinically used filters several studies have shown that cytokines can be evaluated using microdialysis. In particular IL‐1 β and IL‐6 have been studied [4–8], but also MCP‐1 [9] and tumour necrosis factor (TNF)‐ α [10, 11], the latter limited to animal studies. Recovery is only occasionally examined in these studies and when reported it varies from below 1% to up to 50% depending upon the conditions used.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the size‐limited passage through the micropores in clinically used filters several studies have shown that cytokines can be evaluated using microdialysis. In particular IL‐1 β and IL‐6 have been studied [4–8], but also MCP‐1 [9] and tumour necrosis factor (TNF)‐ α [10, 11], the latter limited to animal studies. Recovery is only occasionally examined in these studies and when reported it varies from below 1% to up to 50% depending upon the conditions used.…”
Section: Introductionmentioning
confidence: 99%
“…Microdialysis is a reliable technique for investigating the kinetics of antibiotics in different tissues, and it has been used on many occasions in various tissues, such muscle, lung, brain, and skin, in both animals and humans (18). However, no microdialysis antibiotic-distribution study has ever been conducted in intraperitoneal fluid to our knowledge, although the technique has been used to monitor intraperitoneal concentrations of markers of ischemia, such as lactate, mainly in pigs (13,22,24), but also in humans (8,19) and rats (2,10,11,12).…”
mentioning
confidence: 99%
“…Commercially available microdialysis probes with 100-kDa MWCO membranes have been reported for in vivo microdialysis of a few select cytokines [12][13][14]. The use of particle-based immunoassays has potential to be highly advantageous to the sample-limited microdialysis process since several analytes can be analyzed in a single low volume sample.…”
mentioning
confidence: 99%